Labor Productivity and Labor Compensation in North Macedonia: Sectorial Approach - Trpeski, Predrag; Trenovski, Borce; Kozheski, Kristijan; Merdzan, Gunter (Ss Cyril and Methodius University in Skopje, Faculty of Economics - Skopje, 2022)
Starting from the mid-1970s, there has been a significant disbalance in labor markets in almost all world economies. The postulates of classical economics that the causality between labor productivity and workers' compensation is positive, and that the increase in marginal labor productivity is followed by a directly proportional increase in workers' compensation, no longer stand on solid foundations. In the last few decades, there has been a significant distortion of the functional distribution of income, especially between labor and capital. The widely held thesis that "a rising tide will lift all boats," implying that increased labor productivity will be equally distributed among workers, is becoming less relevant. The world, especially EU economies notice a significant disruption in the relationship between productivity growth and labor compensation. In the paper, an attempt is made to analyze the state of the labor market in the Republic of North Macedonia, through the prism of productivity and labor compensation. Given the fact that there are significant differences in the degree of efficiency and productivity in individual sectors, this analysis focuses on the relationship between the distribution of productivity and labor compensation in different industries. Based on the results of the study, the Republic of North Macedonia exhibits the phenomenon of Reverse Decoupling, where the trend of labor productivity lags behind the trend of workers' compensation. In contrast, productivity and workers' compensation show significant differences by different sectors.
Keywords: Labor productivity; compensation; Great Decoupling